2019
DOI: 10.1021/acs.inorgchem.8b03552
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Synthesis to Identify a Potent, Necrosis-Inducing Rhenium Anticancer Agent

Abstract: Combinatorial synthesis can be applied for developing a library of compounds that can be rapidly screened for biological activity. Here, we report the application of microwave-assisted combinatorial chemistry for the synthesis of 80 rhenium­(I) tricarbonyl complexes bearing diimine ligands. This library was evaluated for anticancer activity in three different cancer cell lines, enabling the identification of three lead compounds with cancer cell growth-inhibitory activities of less than 10 μM. These three lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 101 publications
1
52
0
Order By: Relevance
“…[6][7][8][9][10][11] In this context,our group has been exploringthe anticancera ctivity of polypyridyl rhenium(I) tricarbonyl complexes. [12][13][14][15] Certain members of this class of compounds exhibit potent cytotoxic activity,w hich can be leveragedf or their use as anticancer agents. [16][17][18][19][20][21][22][23] Here, we describe our investigation of an ew rhenium(I) tricarbonyl complexb earing ac helating polypyridyl liganda nd an axial isonitrile ligand as ap otent anticancer agent.O ur efforts to understand the mechanismo f actiono ft his tricarbonyl rhenium isonitrile polypyridyl (TRIP) complex ( Figure 1) have revealed that it is an effective ER stress-inducing agent with significant antiproliferativeactivity.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11] In this context,our group has been exploringthe anticancera ctivity of polypyridyl rhenium(I) tricarbonyl complexes. [12][13][14][15] Certain members of this class of compounds exhibit potent cytotoxic activity,w hich can be leveragedf or their use as anticancer agents. [16][17][18][19][20][21][22][23] Here, we describe our investigation of an ew rhenium(I) tricarbonyl complexb earing ac helating polypyridyl liganda nd an axial isonitrile ligand as ap otent anticancer agent.O ur efforts to understand the mechanismo f actiono ft his tricarbonyl rhenium isonitrile polypyridyl (TRIP) complex ( Figure 1) have revealed that it is an effective ER stress-inducing agent with significant antiproliferativeactivity.…”
mentioning
confidence: 99%
“…The bioinorganic community has explored the use of coordination and organometallic compounds as inhibitors or as auxiliary groups to augment existing organic moieties, [17][18][19][20][21][22] and some of these metal-containing inhibitors having entered clinical trials, such as ferroquine. 23,24 A few uses of organometallic groups to augment existing organic inhibitors have produced spectacular results, including highly selective and active kinase inhibitors.…”
Section: Metallofragment Library Designmentioning
confidence: 99%
“…Complexes similar to those in Classes F and G with bidentate N,N donors have been investigated for their anticancer properties. 22,36 Classes H and I are carbene complexes; most reported biologically active metal-carbene complexes are prepared with Ag(I) and Au(I) and have shown anticancer and antimicrobial properties. that octahedral complexes in the library containing asymmetric bidentate ligands (Classes G and K) form enantiomeric mixtures due to different binding orientations of the bidentate ligand.…”
Section: Metallofragment Library Designmentioning
confidence: 99%
“…The anticancer activity of fac-[Re(CO)3] + compounds has been tested on several different cancer cell lines. The majority of the studies were focused on antiproliferative effects on cervical, 30-33, 47, 51, 57-61 ovarian, 62,63 breast, 12,20,25,[64][65][66] and epithelial adenocarcinoma 24,49,67,68 cell lines showing IC50 values as low as e.g. 0.1 (HeLa), 30 1 (MCF-7), 15 0.75 (A549), 67 4 (NB69 and H4 cells) μM.…”
Section: In Vitro Anticancer Activity Evaluationmentioning
confidence: 99%